Bank efficiency and stock returns in selected ASEAN countries - Chan, Sok-Gee; Karim, Mohd Zaini Abd (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
This paper examines the relationship between bank efficiency and stock returns in selected ASEAN countries for the period 1987-2007.We first estimate the cost and profit efficiency of the sample of listed banks using the non-parametric Data Envelopment Analysis (DEA) approach. We then test both variables for co-integration and estimate the panel vector error-correction model to examine the long and short-term relationship between a bank’s efficiency and stock returns. The results show that a bank’s stock returns prices are co-integrated with both cost and profit efficiency, suggesting a long-term relationship between the two. The results also indicate the superiority of profit efficiency relative to cost efficiency in predicting stock returns in the ASEAN countries. Overall, we conclude both cost and profit efficiency contains useful information for shareholders who wish to explain bank stock returns
Argumenta Oeconomica, 2014, Nr 2 (33), s. 5-21
Keywords: Bank efficiency; stock returns; Data Envelopment Analysis; panel time-series